Rancang Bangun Aplikasi Penggajian Karyawan Pada UMKM Sablon Garment Surabaya - Praditya, Khofifa; Nurcahyawati, Vivine; Soebijono, Tony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Salary is one thing that is very important for UMKM Sablon Garment Surabaya primarily to employees as salary serves as the remuneration received by employees for work that has been done. By giving the employee's salary will be motivated to work. In terms of payroll data is data related to be complete, the data should not be lost and the data must be stored properly. Currently UMKM Sablon Garment have some problems that do not have data recorded with good employees, recording presence inaccurate and does not have a salary slip as proof of receipt of wages. To fix these problems needs to be created payroll application that produces some of the reporting of such reports employee data, payroll reports, reports of borrowing, attendance report. Of the employee payroll application is expected that the stored data will be controlled well and produces an accurate calculation of salaries. Keywords: Application,Employee Salary